Researching of the influence of mechanical stresses on magneto-optical properties of iron borate crystal - Turayev A.A.; Hamrayev J.H. (Global Scientific Publishing, 2022)
Magneto-optical visualization methods are based on the phenomenon of rotation of the plane of polarization of light reflected from a magnetized material (Kerr effect) or passing through a magneto-optical medium (Faraday Effect). Among them, the most promising methods for the study of magnetic carriers are the methods of visualization of the magnetic fields of carriers using films of ferrite garnets. A film of ferrite garnets is grown on a gallium gadolinium garnet substrate, the upper face of which is clarified to increase the contrast of the observed pattern. From below, a mirror-protective layer is applied to the crystal to increase its wear resistance and reflection coefficient
Keywords: magneto-optics; magnetic hysteresis; diamagnetism